Kanaad-The First Propounder of Atomic Theory - Prashad, Jagdish; Suri, Ranjana; Guglani, Uttkanthha; Gupta, Shailey; Gupta, Shilpi (Asian Journal of Chemistry, 2010)
Dalton enunciated his atomic theory in early nineteenth century. Kanaad gave atomic theory about two thousand years ago.